Small Hive Beetle, Aethina tumida (Murray) - Malcolm T. Sanford (EDIS, 2002)
This document is EENY-094, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999.